Strategi Pengembangan Sekolah di Era Globalisasi dalam Konteks Manajemen Berbasis Sekolah - Juniaris Agung Wicaksono; Semin Semin; Puthut Waskito (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2023)
Education is believed to be the main means of developing the quality of human resources. It is in this context that revitalization of education policy continues to be the government's concern. So that a form of revitalization emerged, the issue of centralization to decentralization which had previously been raised as an effort to empower the region. Encouraged by the changing state of the nation's politics, it is increasingly believed that one of the important efforts that must be made is to improve the quality of education. in which the education unit is given authority and delegation of school authority to carry out continuous improvement and quality improvement. Management is a political approach that aims to reorganize school management by giving power to school principals and increasing community participation in efforts to improve school performance, which includes teachers, students, school principals, parents, and the community. The hope is that with this school-based education management system, the quality of education can be improved and that the participation of the community and the initiatives of educational institutions at the micro (school) level will increase. Based on the management of educational quality, which is built through five pillars: independence, partnership, participation, openness, and accountability